Peripheral mononuclear leukocyte DNA damage, plasma prolidase activity, and oxidative status in patients with benign prostatic hyperplasia. (July 2015) - Gecit, Ilhan; Meral, Ismail; Aslan, Mehmet; Kocyigit, Abdurrahim; Celik, Hakim; Taskın, Abdullah; Kaba, Mehmet; Pirincci, Necip; Gunes, Mustafa; Taken, Kerem; Demir, Halit; Uyuklu, Mehmet; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Prolidase plays a major role in collagen turnover, matrix remodeling, and cell growth. Benign prostatic hyperplasia (BPH) may be associated with an increased extracellular matrix deposition. Therefore, the present study was designed to investigate the plasma prolidase activity, oxidative status, and peripheral mononuclear leukocyte DNA damage in patients with BPH. Patients and methods Twenty-six male patients with BPH and 24 healthy male subjects were included in this study. Blood samples were collected from antecubital vein after an overnight fasting period, and the plasma was separated. Plasma prolidase activity, total antioxidant capacity (TAC), total oxidant status (TOS), and oxidative stress index (OSI) were determined. The peripheral lymphocyte oxidative DNA damage was determined using an alkaline single cell gel electrophoresis assay (comet assay). Results The plasma prolidase activity, TOS levels, OSI values, and peripheral mononuclear leukocyte DNA damage were significantly higher (P < 0.001), while the TAC levels were significantly lower (P < 0.001) in patients with BPH than controls. In BPH patients, the prolidase activity was significantly associated with TAC levels (r = −0.366, P < 0.05), TOS levels (r = 0.573, P < 0.001), and OSI (r = 0.618, P < 0.001) and peripheral mononuclear leukocyte DNA damage (r = 0.461, P < 0.001). Conclusions Our results showed that BPH might be associated with an increased oxidative stress, and also an increased plasma prolidase activity. Increased prolidase activity might play an important role in the etiopathogenesis and/or progression of BPH.